Formulation and development of Commiphora myrrha based polyherbal nanoemulsion mouthwash and assessment of its anti-oxidant and cytotoxicity activity - Yusof, Norafiqah; David, Sheba R; Mumin, Nuramalina H; Ahmad, Liyana; Rajabalaya, Rajan (Journal of Applied Pharmaceutical Research, 2024)
Background: A Commiphora myrrha (CM)-based polyherbal mouthwash with enhanced stability and oral bioavailability was developed using a high-energy homogenization method. Methodology: The formulations primarily consist of herbal extracts from CM, ginger, and white tea, optimized based on various parameters, including organoleptic properties, pH, Dynamic Light Scattering (DLS), and Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR- FTIR). Stability studies were also conducted on each formulation. Results and Discussion: The particle sizes ranged from 77 to 216 nm, with zeta potential values between -0.92 and -2.09 ± 0.38 mV, indicating stability. ATR- FTIR studies confirmed no interaction between the ingredients. Antioxidant activity was significant, with IC50 values for pure extracts of CM, white tea, and ginger being 0.071 ± 0.003, 0.073 ± 0.004, and 0.066 ± 0.004 mg/ml, respectively. For formulations M1 and M2, IC50 values were 1.030 ± 0.901 and 0.495 ± 0.496 mg/ml, respectively, showing a concentration-dependent increase in antioxidant activity. The MTT cytotoxicity assay showed high cell viability for M1 (96.1%) and M2 (133.3%) at 0.002 mg/ml, suggesting low cytotoxicity, though variability in results indicated further assay optimization. High standard deviations, 0.06 and 0.208, indicated limitations in experimental conditions emphasizing the need for improved assay parameters for accuracy. Conclusion: The mouthwash formulations, M1 and M2 Show promise, with future work focusing on increasing CM concentration and refining cytotoxicity testing methods to ensure reliable data for subsequent antibacterial and in vivo studies.